PHENOMENOLOGICAL UNDERSTANDING OF M. WEBER’S POSTULATE OF SUBJECTIVE INTERPRETATION IN A. SCHÜTZ’S WORK - Popić, Snežana S. (Politeia, 2021)
Max Weber, as the founder of interpretative sociology, left a significant influence on phenomenological, that is, reflective sociology. His concept of understanding (Verstehen) gained a modified role in the sociological theoretical-methodological directions that emerged during the twentieth century. Understanding is not only a methodological procedure of interpreting social reality but also a condition of its intersubjectivity as a special experiential form. Therefore, in this paper, the theoretical schemes and methodological strategies of Max Weber and Alfred Schütz are problematised with the central attention to the use of the postulate of subjective interpretation. This postulate is presented within the phenomenological sociological model, primarily in the sense of the general principle of constructing types of flow-actions,  that is, the typification necessary for social harmonisation of participants in the common-sense world. Since the model of scientific constructs is based on the model of common sense constructs as first-order constructs, this postulate also gained its central place in the methodological sense, as one of three possible forms – experiential, epistemological, and methodological. In the wake of all previously analysed, the specificity of the phenomenological understanding of the concept of action is also pointed out.
Keywords: Max Weber; Alfred Schütz; subjective interpretation; action; phenomenology